Health literacy assessment and analysis of influencing factors in pregnant women with gestational diabetes mellitus in Southwest China - Tang, Fangmei; Gu, Li; Guo, Xiujing; Fu, Wenjing; He, Benyi; Song, Yuqing; Li, Dehua (Frontiers in Public Health, 2025)
ObjectiveThe main objectives of our study are evaluating the health literacy level among women with gestational diabetes mellitus (GDM) in Southwest China and explore the influencing factors, using a multidimensional health literacy assessment scale (Chinese version of the HLS-14). Given that the HLS-14 has not been used in GDM previously, its reliability and validity testing was included as a secondary objective.MethodIt was a cross-sectional survey with 565 GDM pregnancies. The Maternal and child health information access questionnaire, Chinese version of the HLS-14, Perceived Social Support Scale (PSSS) and General Self-efficacy Scale (GSES) was used to collect health information access behaviors, health literacy, social support and self-efficacy levels, respectively. SPSS 21.0 was used for descriptive statistical, multiple stepwise linear regression analysis and exploratory factor analysis (EFA). Amos 26.0 was used for confirmatory factor analysis (CFA).ResultsThe Chinese version of HLS-14 has good reliability and validity in GDM pregnancies. The Cronbach’s α are 0.849, 0.866, 0.859, and 0.883, respectively. The exploratory factor analysis extracted three common factors with a cumulative variance contribution rate of 68.405%. The confirmatory factor analysis model fit was good (χ2/df = 2.595, RMSEA = 0.055, IFI = 0.970, TLI = 0.963, CFI = 0.970). The HL level in pregnancies with GDM was moderate with a mean score of 3.26 ± 0.41, of which 24.10% had limited HL, 41.87% had moderate HL, and 34.03% had adequate HL. Regression analysis showed that the women with higher family support (β = 0.298, p < 0.001), recording pregnancy management diary (β = 0.199, p < 0.001), higher the family income (β = 0.140, p < 0.001), lower pre-pregnancy BMI (β = −0.116, p = 0.004), longer time spent searching for health information (β = 0.111, p = 0.006), and searching for health information through a medical health information website (β = 0.093, p = 0.019) had higher HL levels. These variables explained 23.1% of the variance in HL.ConclusionThe Chinese version of the HLS-14 has good applicability in the GDM pregnancies. The HL level of them is moderate, needs to be improved. Healthcare professionals should focus on the GDM population with low family income and high pre-pregnancy BMI, fully mobilize their social support system, provide reliable access to information, encourage all GDM pregnancies to use pregnancy management diaries to record their self-management behaviors, and ensure the effectiveness of health education.